Obtaining Starch from two Varieties of Taro: Colocasia esculenta L. and Xanthosoma sagittifolium L, through the Application of three Chemical Methods - Sánchez Llaguno, Sungey Naynee (2023)
Taro (Colacasia esculenta L.), due to its accelerated vegetative development and easy propagation, has become one of the main crops in the tropical areas of Ecuador. Thanks to its biochemical properties and its high nutritional value, it has allowed the application of simple technologies to take advantage of this agricultural resource to obtain starch for use in different foods. The objective of this research was to obtain starch from two varieties of taro Colocasia esculenta L and Xanthosoma sagittifolium L, through the application of three chemical methods (citric acid, hydrochloric acid, phosphoric acid), in which a process of decantation and centrifugation. An ANOVA was applied, with a completely randomized block design using A*B*C factorial arrangement, obtaining a total of 12 treatments and 3 repetitions. The statistical differences between the means of the treatments were established with the Tukey test (P>0.05). A higher yield was obtained in the Malanga Blanca + Centrifugation + Citric Acid 29.34% treatment, in what corresponds to acidity and pH, the values were within those established by similar works, the highest fiber percentage was presented in the purple Malanga treatment + Decantation + Phosphoric acid (0.68%), while the humidity is within the permitted parameters of the INEN 616, which indicates 14% and an optimal gelatinization temperature in the white Malanga treatment + Decantation + Phosphoric acid (56.53°C).